The Impact of The Existence of Generator of Steam Power Electric Toward in Sukra Sub-District Indramayu - Abdurohim, Siha; Astuti, Tri Marhaeni Pudji; Setyowati, Dewi Liesnoor (Universitas Negeri Semarang, 2018)
Sumuradem is an area located on the north coast with the peculiarities of rural communities who work as farmers. Social and cultural relations of the community are built like rural communities in general. Observation in the village of Sumuradem shows that people experience socio-cultural changes due to the existence of the steam power plant. This study aims to (1) Know and analyze the activities of social and cultural life of society before and after the existence of PLTU, (2) Knowing and analyzing the impact of power plant existence on socio-cultural changes Sumuradem. The method used is qualitative method. Methods of data collection by way of observation, interviews, and documentation. Technique of data validity by using source triangulation and theory. The study is located in the village of Sumuradem, Sukra District, Indramayu District. Sources of research data are informants consisting of the village head of Sumuradem, youth leaders, community leaders, religious figures, and the Sumuradem community. The method used is qualitative method. Methods of data collection by way of observation, interviews, and documentation. Technique of data validity by using source triangulation and theory. The study is located in the village of Sumuradem, Sukra District, Indramayu District. Sources of research data are informants consisting of the village head of Sumuradem, youth leaders, community leaders, religious figures, and the Sumuradem community. The results showed that: (1) Changes in social interaction of Sumuradem community occurred before and after the existence of steam power plant which is seen from the social interaction interaction among society, due to new activity. People's lifestyles changed after the power plant became more modern with the level of fulfillment of higher needs. (2) PLTU gives positive impact to socio-cultural change of society. Suggestion of researcher so that society can accept socio-cultural change, but must still maintain the existing culture. For example mutual respect, gotong royong in the community, addressing socio-cultural changes with a positive. The various facilities offered from the existence of power plant, the community must be selective in sorting them to be appropriate.